Optimisation of the chemical oxidation reduction process (CORD) on surrogate stainless steel in regards to its efficiency and secondary wastes - Rivonkar, Aditya; Katona, Richárd; Robin, Mathurin; Suzuki-Muresan, Tomo; Abdelouas, Abdessalam; Mokili, Marcel; Bátor, Gergő; Kovács, Tibor (Frontiers in Nuclear Engineering, 2022)
Nuclear Power is a decarbonated method of electrical energy generation. Using nuclear energy as a power source is currently considered as the best option in the fight against climate change. But the radioactive waste generated from nuclear power plants and their related facilities are cause of concern. Though the high level and intermediate level activity wastes are contained in small volumes (≤10), significant volumes of lower activity wastes are generated. Metallic wastes are a major component of these radioactive wastes with about 500,000 tons expected in France alone, including 130,000 tons from steam generators. Majority of these metals are made of Stainless steel 316 alloy or Inconel 600. Under the effect of the primary circuit water and irradiation, these components corrode and the corrosion products may be activated when close to the fuel, and be transported throughout the circuit. These products can be deposited on the surface of other metal components, causing contamination of the latter. The contamination can be adsorbed on the surface but can also diffuse in the oxide layers and sub-surface. The oxide layer is composed of an inner layer of Cr oxide under a layer of Ni and Fe oxide. Chemical decontamination is preferred due to the possibility of decontamination of difficult geometries and tube bends. In order to decontaminate these materials, it is important to dissolve the oxide layers chemically and a few micrometres of base metal where it could have diffused. An existing chemical method used to treat these materials is studied in this article, Chemical Oxidation Reduction Decontamination(CORD). Surrogate steel samples were prepared using high temperature induction heating and water vapour after sample preparation and cleaning. The oxide layer was characterised before treatment of the samples in the batch method at different concentrations and its are observed on the dissolution of the oxide layers. A protocol is being developed for the treatment of secondary waste effluents by multi-stage precipitation with a goal to reduce the total waste volumes and volumes of ion exchange resins that would otherwise be needed.